Distracted Institutional Investors. (December 2019) - Schmidt, Daniel
Abstract : I investigate how distraction affects the trading behavior of professional asset managers. Exploring detailed transaction-level data, I show that managers with a large fraction of portfolio stocks that have an earnings announcement are significantly less likely to trade in other stocks, suggesting that these announcements divert attention from trading decisions for other stocks. This distraction effect is more pronounced for nonpassive managers who engage in active stock selection choices. Finally, I identify three channels through which distraction hurts managers' performance: Distracted managers trade less profitably, incur slightly higher transaction costs, and are less likely to close losing positions.